Biological and physical characterization of the seabed surrounding Ascension Island from 100–1000 m. (19th July 2017) - Nolan, E.T.; Barnes, D.K.A.; Brown, J.; Downes, K.; Enderlein, P.; Gowland, E.; Hogg, O.T.; Laptikhovsky, V.; Morley, S.A.; Mrowicki, R.J.; Richardson, A.; Sands, C.J.; et al.
Abstract : Recent studies have improved our understanding of nearshore marine ecosystems surrounding Ascension Island (central Atlantic Ocean), but little is known about Ascension's benthic environment beyond its shallow coastal waters. Here, we report the first detailed physical and biological examination of the seabed surrounding Ascension Island at 100–1000 m depth. Multibeam swath data were used to map fine scale bathymetry and derive seabed slope and rugosity indices for the entire area. Water temperature and salinity profiles were obtained from five Conductivity, Temperature, Depth (CTD) deployments, revealing a spatially consistent thermocline at 80 m depth. A camera lander (Shelf Underwater Camera System; SUCS) provided nearly 400 images from 21 sites (100 m transects) at depths of 110–1020 m, showing high variability in the structure of benthic habitats and biological communities. These surveys revealed a total of 95 faunal morphotypes (mean richness >14 per site), complemented by 213 voucher specimens constituting 60 morphotypes collected from seven targeted Agassiz trawl (AGT) deployments. While total faunal density (maximum >300 m −2 at 480 m depth) increased with rugosity, characteristic shifts in multivariate assemblage structure were driven by depth and substratum type. Shallow assemblages (~100 m) were dominated by black coral ( Antipatharia sp.) on rocky substrata, cup corals ( Caryophyllia sp.) and sea urchins ( Cidaris sp.) were abundant on fine sediment at intermediate depths (250–500 m), and shrimps ( Nematocarcinus spp.) were common at greater depths (>500 m). Other ubiquitous taxa included serpulid and sabellid polychaetes and brittle stars ( Ophiocantha sp.). Cold-water corals ( Lophelia cf. pertusa ), indicative of Vulnerable Marine Ecosystems (VMEs) and representing substantial benthic carbon accumulation, occurred in particularly dense aggregations at <350 m but were encountered as deep as 1020 m. In addition to enhancing marine biodiversity records at this locality, this study provides critical baseline data to support the future management of Ascension's marine environment.